Review on Development of Oxygen/Nitrogen Separations Technologies - Fatin Nurwahda, Ahmad; Norazlianie, Sazali; Mohd Hafiz Dzarfan, Othman (Akademi Baru, 2019)
Various industrial sectors such as chemical, medical and upgraded combustion operations are demanding for the oxygen-enriched gas. Pressure swing adsorption and cryogenic distillation are the well-known approaches used for oxygen-nitrogen separation that capable to produce a large daily volume of oxygen with high purity. Nevertheless, these technologies are not preferable due to their high energy consumption. Therefore, membrane technology is introduced as an alternative method to separate gas since it has advantages compared to other approaches in the context of energy consumption. Since this alternative technology is cost-effective, abundant of researches have been carried out to develop membranes with surpassing oxygen-nitrogen separation performance that meets the specifications for industrial applications. The objectives of this paper are to analyze the traditional technologies and membrane technology for oxygen-nitrogen separation, the latest procedures and precursors materials used in fabricating the membranes, including the recent study of membrane performance for oxygen-nitrogen separation.